TRANSPLANTASI KARANG DITUBIR PADA AREA PATAHAN KARANG (RUBBLE) BEKAS PENGEBOMAN IKAN DI DESA SAWAPUDO - Almuqni, Bobby Akhyan; Setiawan, Haris; Tamsil, La Ode (Program Kreativitas Mahasiswa - Penelitian, 2013)
This study to determine the success of transplantation techniques are directly applied to the area of rubble, the former fish bombing, to manipulate the substrate is unstable / shaky so it can be used as a medium for transplantation. Research is planned to last for 5 months. The research is based on completely randomized design with water depths as treatment. On nets placed at a depth of 3 meters in length t get the initial seed coral as follows: 73.2 mm, 54.6 mm, 103 mm, 74.5 mm, 83.7 mm, 110.4 mm, 51.2 mm, 67.8 mm 98.5 mm. t the beginning of this term would represent, a basic reference specimens to determine the growth rate of coral transplants.Â Keywords : Transplantation, Rubble, net scrap, Used Bombing